PERANCANGAN MEDIA PROMOSI RESTO KAMPOENG STEAK DENGAN KARAKTERISTIK SURABAYA SEBAGAI UPAYA MENINGKATKAN BRAND LOYALTY - Mirani, Ananda Kurnia; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal ArtNouveau, 2013)
Kampoeng Steak (KS) is one of the local restaurant franchise from Surabaya. However this food business is not able to display a uniqueness, such as the characteristics of Surabaya. Where as, if this uniqueness can be shown then this restaurant would have more value, especially when opening branches ini major cities outside Surabaya. Altough KS already show a little bit element of Surabaya, people still do not really care. So that KS imaging as one of the restaurant from Surabaya not been delivered. Then an appropriate strategy shall be made to express characteristic from KS. So that KS remains the peopleâs choice among ather steak culinary business. From these problems, this research focused on the design of a media promotion KS restaurant by using the characteristics of Surabaya as an effort to increase brand loyalty. With this media promotion KS will have an unique and distinct identity, which will form the consumer perception so that the product will more be known to the public.